2018
DOI: 10.24869/psyd.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Risk in Attention-Deficit/Hyperactivity Disorder

Abstract: Although differences in studies design and samples made the results difficult to compare and interpret, many studies indicate an association between ADHD and suicidal behavior. It remains controversial whether there is a direct relationship or whether the association depends on the increased prevalence of pre-existing comorbid conditions and individual and family dysfunctional factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 82 publications
1
27
0
4
Order By: Relevance
“…Socio-emotional maladjustment may exacerbate problems with executive functions and inattention in this population, setting in motion a vicious cycle between cognitive and emotional difficulties (Habib & Naz, 2015;Lima, de Azoni, & Ciasca, 2011). Additionally, research has suggested that youth with LD/ADHD may be at increased risk of suicidal thoughts and attempts (Giupponi et al, 2018;James, Lai, & Dahl, 2004;McBride & Siegel, 1997;Svetaz, Ireland, & Blum, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Socio-emotional maladjustment may exacerbate problems with executive functions and inattention in this population, setting in motion a vicious cycle between cognitive and emotional difficulties (Habib & Naz, 2015;Lima, de Azoni, & Ciasca, 2011). Additionally, research has suggested that youth with LD/ADHD may be at increased risk of suicidal thoughts and attempts (Giupponi et al, 2018;James, Lai, & Dahl, 2004;McBride & Siegel, 1997;Svetaz, Ireland, & Blum, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to these findings, a Swedish cohort study (total number of samples 1599, mean age over 70 years) using the Wender Utah Rating Scale (WURS), reported that there was no substantially elevated mortality risk in individuals who retrospectively scored higher than WURS cut-off score for ADHD diagnosis [58]. Mortality in ADHD patients is also linked to suicidal behavior [59]. While it remains unclear whether there is a direct relationship between the suicide and ADHD in adults, ADHD symptom severity has been associated with an increased risk for suicidal behavior [60].…”
Section: Developmental Trajectory Of Adhdmentioning
confidence: 93%
“…There is an evolving literature linking ADHD with increased risk of suicide; however, causality has not been established. It was previously hypothesised that factors such as comorbid psychiatric disorder and family factors may account for this increased risk 1…”
Section: Commentarymentioning
confidence: 99%